Evolution and assessment of biomarkers in perioperative and critical care medicine - Md Ralib, Azrina; Aidid, Afif Hakimi; Mohd Nor, Mohd Amiruddin; Aziz, Ahmad Akmal; Soo, Ki Yang (Malaysian Society of Anaesthesiologists, 2021)
explains how biomarkers are evolving from simple lab tests to multidimensional tools for risk prediction and organ‑specific monitoring in perioperative and ICU patients. They now support diagnosis, risk stratification, early detection of organ injury, and treatment guidance, especially in cardiovascular risk, kidney injury, and sepsis.​